Factores estresores frente al proceso pre-quirúrgico que generan niveles de ansiedad en pacientes sometidos a una cirugía electiva en el Hospital Manuel Ygnacio Monteros de Loja periodo enero a julio 2014 - Rodríguez Gaona, Yanela Lisbeth (2015)
The present research was done with the purpose of: identify the relationship between the stressor factors facing the pre-surgical process with anxiety levels on patients subjected to a elective surgery in “Manuel Ygnacio Monteros city of Loja"hospital. Is a observational descriptive study, correlational bibliographic; whose universe of patients hospitalized male and female of programmed surgery in the “Manuel Ygnacio Monteros” hospital taking 50 patients of which 42 present anxiety in ages between 20 and 70 years old and patients who can also answer the given questions. The Hamilton anxiety test was given Volicer and Bohanon stressor factors to evaluate the stress and find out the main stress factors the patients subjected to selective surgery have. According to the researches, exist female predominance with high and critical anxiety levels, being the 51-60 ages the most affected, among the stressor factors more frequent in the process pre-surgical that generates more anxiety levels due to a stress are: having no one to visit him, thinking that the surgery is painful, followed by the physical aspect after the surgery, the awkwardness when it comes to eat and the fact to spend your time with a sick person in recovery. It's necessary psychological preparation plan prior to surgery is highly recommend, practicing the relaxation techniques to help lower the anxiety levels. KEY WORDS: Pre-surgical, anxiety, surgery and stressor factors.